PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PT. BANK MANDIRI, Tbk PERIODE 2009-2014 - Ida Zuniarti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Capital is one of very important factors for a business unit to keep its business run well, because by using its capital sources properly then the operational activity of the company is able to operate successfully.  The fulfillment of funds to have capital of a business unit can be provided either from internal or external sources.  The internal supply of funds come from the internal part of the company, otherwise for the external supply of funds can be gained from capital and money market.  The company management must be able to determine precisely about the capital structure which will be used since the decision making of the source over the funding is a very important thing.  The company decision in regarding the optimum capital, can commensurate between risk and benefit. This research is aimed to understand whether the impact of measured capital structure using Debt to Equity Ratio (DER) towards financial performance measured by using the Return on Equity (ROE) in PT Bank Mandiri, Tbk.The research data being used is a secondary data taken from published financial statements namely income statement and balance sheet obtained by Bank Indonesia through the web pages www.bi.go.id and from the website of Bank Mandiri ; www.bankmandiri.co.id using simple linear regression analysis method.  The result of the research showed that the variable of DER is not significantly effected towards ROE in PT Bank Mandiri, Tbk time period starting from January – December 2009 to December 2014.      Keywords : Financial Performance, Equity Structure, ROE, DER